Lexical variation of traditional snack naming in Palang Subdistrict, Tuban Regency - Sapanti, Intan Rawit; Perihatin , Ayu Andika; Purnawan, Kadek (BAHASTRA, 2022)
This article discusses the lexical variations of the Javanese language in traditional snack name in Palang subdistrict, Tuban Regency. The reason for choosing this object of research, is to explain the dialect variation especially in traditional snack naming among the society and to explain the reasons of lexical variation. This article focusses on two research questions, (1) Lexical variation on traditional snack name in Palang subdistrict, Tuban Regency, (2) The causative factor of lexical variations. This research used qualitative descriptive. The data of 45 gloss traditional snack name were collected through 19 observation point from 19 village in Palang subdistrict using field method and proficient method. The research funding of this article found the lexical variations on traditional snack naming are as follows; 1) Group without variation (22 gloss), 2) Group with variations (18 gloss) which consists of 2, 3, 4 and 6 form of lexical variations. The causative factor of the lexical variations due to the way of living and geographic factor.